Digital Transformation Sustainability in Indonesia's Banking Sector: A Systematic Review - Tiara Aprilia Kardiman; Rizki Yoga M; Farida Indriani (LifeSciFi, 2025)
This systematic review explores how digital transformation in the Indonesian banking sector contributes to sustainable growth through innovation, strategic adaptation, and policy alignment. Drawing on nine peer-reviewed articles published between 2020 and 2025, the study synthesizes evidence from databases such as Scopus, Web of Science, and Google Scholar, using Publish or Perish to support data collection. An initial 500 articles were identified, and after rigorous screening and quality assessment, nine peer-reviewed articles were selected based on thematic relevance and methodological robustness. The findings reveal that digital tools – including mobile banking, AI, blockchain, and digital infrastructure – improve operational efficiency, financial inclusion, and resilience in banking institutions. The review identifies five thematic research clusters: digital innovation strategies, economic and environmental sustainability, empirical performance evaluation, systemic challenges, and local implementation. These themes collectively demonstrate how digital transformation acts as a strategic enabler for inclusive economic development in Indonesia. The study highlights the importance of policy innovation, SME integration, and digital literacy programs while noting the limited number of Indonesia-specific empirical studies as a major limitation. Future research should use a longitudinal and mixed-method approach to better capture the evolving digital trends in the Southeast Asian financial sector.